The Barangay-based exercise as a training technique - Bonifacio, Manuel Flores (Philippine Journal of Public Administration, 1980)
Field Practice, a three-unit course required of graduate students of the Institute of Public Health, University of the Philippines System, is a practicum whereby the students apply the basic knowledge and skills gained to actual community situations by integrating with the community and other health workers. Undoubtedly, the course has made a significant impact on the students, the faculty, and the community. Exposure of the students to actual health problems has rounded up their formal academic training and has developed in them an understanding of the challenges and demands of health care delivery. To the faculty preceptors, field practicum has enriched their teaching repertoire. And to the community-the recipients of health service-the course has generated in them a positive concern with their health needs and a commitment to improve their quality of life.